Analisis Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah (Dprd) Di Kabupaten Siak Dalam Perspektif Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Handi, Dian Mega; Zulwisman, Zulwisman; HB, Gusliana (Jurnal Ilmiah Wahana Pendidikan, 2024)
The function of the DPRD regarding authority in terms of supervision over the implementation of Regional Regulations is also regulated in Article 101 Paragraph (1) C of Law Number 9 concerning the second amendment to Law Number 23 of 2014 which reads: "The Provincial DPRD also has duties and authority carry out supervision over the implementation of Provincial Regional Regulations and the Provincial APBD”. Therefore, the aim of this thesis research is first, to find out the supervision of the Regional People's Representative Council (DPRD) in Siak Regency in the perspective of Law Number 23 of 2014 concerning Regional Government. Second, to find out the influencing factors of the Regional People's Representative Council (DPRD) in Siak Regency in improving the supervisory function. Third, to find out the efforts made by the Regional People's Representative Council (DPRD) in Siak Regency to improve its supervisory function. This type of research is classified as a qualitative research type. This research uses secondary data consisting of primary legal materials, secondary legal materials, tertiary legal materials and data collection techniques carried out using library research methods, then qualitative analysis is carried out. From this research there are three main things that can be concluded. First, what needs to be considered is the implementation process. The responsibility of DPRD members to carry out supervision and guidance is a crucial aspect of their role. They must ensure that appropriate oversight is in place to maintain the integrity and effectiveness of their organizations. Second, . Factors that hinder the effective implementation of the DPRD's duties and functions include limited human resources (HR) for Siak district DPRD members who only have little and limited political experience, inadequate supporting facilities and infrastructure and an inadequate budget. Third, Siak Regency DPRD's supervision of the 2016 to 2019 APBD was carried out through field visits and hearings with work unit leaders. This inspection is carried out in three stages, namely the planning stage, implementation stage and accountability stage. Author's suggestions First, to increase the capacity of the DPRD in carrying out its main tasks and functions, this institution positions itself more professionally and independently as an organization outside the executive agency that has a supervisory function. Second, we hope that the implementation of the supervisory function of the Siak Regency DPRD can be carried out optimally and effectively so that there is a check and balance between the DPRD and the regulator in implementing it. Third, the way to show DPRD supervision is to provide initial Regional Regulations to the DPRD which outlines the responsibilities for implementing the APBD